Left Ventricular Systolic Function and Diastolic Function Profile in Congestive Heart Failure Patients on Tangerang District General Hospital - Aufa Safira Putri (ARKAVI [Arsip Kardiovaskular Indonesia), 2018)
Heart failure is a clinical syndrome characterized by abnormalities in the structure or function of heart which results in the heart not being able to pump blood for tissue metabolic needs. Heart failure is marked by clinical manifestations in the form of circulatory congestion, tightness, and fatigue. The purpose of this study was to determine the profile of systolic function and left ventricular diastolic function in patients with congestive heart failure using descriptive methods. Data collection was taken from medical records from April to June 2018 at the Tangerang District General Hospital. The highest age is obtained in the range of 61-70 years as many as 16 patients. Based on gender, the proportion of men is at most 64% or 32 patients. Systolic dysfunction (HFrEF) has a proportion of 58% or 29 patients. Diastolic dysfunction with E/A (<1) parameters as many as 50% or 25 patients. Diastolic dysfunction with DT(>200) parameters were 21 patients. Diastolic dysfunction with E / e '(> 13) parameters as many as 31 patients. More patients with reduced systolic function (HFrEF) were 29 patients (58%). The diastolic form that is often found in patients with heart failure is Grade I as many as 25 patients (50%). It can be concluded that most patients with systolic heart failure can be accompanied by various forms of diastolic dysfunction. Keywords: Systolic Function, Diastolic Function, Congestive Heart Failure Gagal jantung adalah sindroma klinik yang ditandai oleh adanya kelainan pada struktur atau fungsi jantung yang mengakibatkan jantung tidak dapat memompa darah untuk memenuhi kebutuhan metabolisme jaringan. Gagal jantung ditandai dengan manifestasi klinik berupa kongesti sirkulasi, sesak dan mudah lelah. Tujuan penelitian ini adalah mengetahui profil fungsi sistolik dan fungsi diastolik ventrikel kiri pada pasien gagal jantung kongestif dengan menggunakan metode deskriptif. Pengumpulan data diambil dari rekam medis dari bulan April sampai Juni Tahun 2018 di Rumah Sakit Umum Kabupaten Tangerang. Didapatkan usia terbanyak yaitu kisaran 61-70 tahun sebanyak 16 pasien. Berdasrakan jenis kelamin, proporsi laki laki paling banyak yaitu 64% ata 32 pasien. Gangguan sistolik HFrEF memiliki proporsi sebanyak 58% atau 29 pasien. Gangguan diastolik dengan parameter E/A <1 sebanyak 50% atau 25 pasien. Gangguan diastolik dengan parameter DT >200 sebanyak 21 pasien. Gangguan diastolik dengan parameter E/e’ >13 sebanyak 31 pasien. Lebih banyak pasien dengan fungsi sistolik yang menurun (HFrEF) sebanyak 29 pasien (58%). Bentuk diastolik yang sering dijumpai pada pasien gagal jantung adalah Grade I sebanyak 25 pasien (50%). Dapat disimpulkan bahwa sebagian besar pasien gagal jantung sistolik dapat disertai dengan berbagai bentuk disfungsi diastolik. Kata Kunci: Fungsi Sistolik, Fungsi Diastolik, Gagal Jantung kongestif